Effect of different attractants used in Olipe traps for olive fly mass-trapping on parasitoids in the Northeast of Portugal. - Porcel, M. (2011)
The hymenoptera parasitoids represent and important beneficial group in olive agroecosystem. Their action maintains certain olive pest species numbers lower than the economic threshold. In this can text, to improve their activity and increase the sustainability of the olive agroecosystem it is necessary to know the negative effect of different agronomic practices in their populations. In ecological production, mass-trapping is an important control method against the olive fruit fly, Bactrocera oleae Gmel., the most serious pest of olives in the Mediterranean countries. The aim of the present work was to study the effect on parasitoids of different attractants used combined with Olipe traps.